(3GdJHUQI aj Yde GdMSGHs - (3GdeXaQ Hf jMji Hf YHGS GdeZQHjs
(3ChdgG (B:s
(3hHYO aEfi deG CMeOJ geI GdbGVi GdEeGe GdCLd fUjQ GdOjf Hf CMeO GdNWjHi COGe Gddg fYegG , hYGjfJ eG efMg ef GdPcGA GdKGbH s
(3BNQgG (B:s
(3deG PcQfGg ai GdHGH GdJGSY ef GdebGdI GdChdi hbO GfJgi HfG Gdbhd Edi TQM LejY eG hYOfG HGdEHGfI Yfg hESJjaGA CbSGe GdCOhGJ GdMSGHjI , adffgi GdebGd gGgfG hfNeJg hGdMeO ddg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3cJHJ GdYfGhjf HNW eLhO Lejds
(3cJHJ GdCQbGe HGdMeQI HChdgG agQSJ ddehVhYGJs
(3hai PjdgG JeQjfGJ MSGHjIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdQjGVjGJs